Analýza vybraných genových polymorfismů a její význam pro individualizovanou farmakoterapii - Řežábková, Kristina (Jihočeská univerzita, 2020)
This thesis deals with the metabolism of xenobiotics and the fact that it may be influenced by genetic polymorphisms in pharmacogens. In the experimental part, samples of volunteers and patients were tested by several methods of molecular biology detecting these polymorphisms and the results were interpreted and compared on the basis of available studies. Furthermore, the work highlights methods that would lead to successful individualized pharmacotherapy in similar clinical trials.
Analysis of selected gene polymorphisms and its importance for individualized pharmacotherapy
Keywords: farmakologie; farmakogenetika; farmakogenomika; metabolismus léčiv; pharmacology; pharmacogenetics; pharmacogenomics; drug metabolism